A cross-sectional study on dentists’ learning preferences for learning about light-curing units and resin-based composites - Afnan O. Al-Zain; Khlood Baghlaf; Omar Abdulwassi; Reem Almukairin; Maram Alanazi; Elaf Alshomrani; Sultan Alftaikhah; Richard B. Price (Saudi Dental Journal)
Introduction: Despite researchers emphasizing the importance of understanding the type, how they should be used, and their effect on restoration longevity, many dentists lack critical knowledge about their light curing units (LCUs). Aim: To identify the parameters dentists use when choosing an LCU or resin-based composite (RBC) and to determine the most effective educational method for dentists to learn about LCUs. Methods: A cross-sectional study used a validated electronic questionnaire targeting dentists, interns, and students in private and government sectors. Demographic data, current LCU practices, parameters for selecting LCUs and RBCs, and the preferred educational methods for learning about LCUs were collected. The three main parameters used to determine participants’ knowledge of LCU selection were brand reputation, irradiance, and LCU wavelength compatibility with the RBC photoinitiator spectrum. Results were analyzed using chi-square test, Fisher’s exact test, and independent sample t-test. Results: A total of 420 participants completed the survey. Only 11 % considered the wavelength as the 1st parameter when selecting an LCU. Participants with graduate degrees were significantly more knowledgeable about the LCU selection parameters than those with bachelor’s degrees (p = 0.009). Dentists who frequently used LCUs knew significantly more about the RBC selection parameters (p = 0.037). Hands-on workshops, in-person lectures, and online lectures were preferred over social media. YouTube is one of the most popular social media platforms. All participants preferred YouTube as the top social media educational resource, with specialists and consultants showing a significantly stronger preference than general dentists, interns, and students (p = 0.036). Conclusion: Few participants thought that the need for the wavelengths emitted by the LCU to be compatible with the absorption spectrum of the photoinitiator used in the RBC was a key parameter when selecting an LCU or RBC. Respondents favored hands-on workshops and in-person lectures over social media to learn about LCUs. Educators should prioritize these methods to enhance understanding the choice and use of LCUs and RBCs within the dental community.